2008
DOI: 10.1111/j.1365-2966.2007.12601.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the properties of the remnants of dissipative galaxy mergers

Abstract: We construct a physically motivated model for predicting the properties of the remnants of gaseous galaxy mergers, given the properties of the progenitors and the orbit. The model is calibrated using a large suite of smoothed particle hydrodynamics (SPH) merger simulations. It implements generalized energy conservation while accounting for dissipative energy losses and star formation. The dissipative effects are evaluated from the initial gas fractions and from the orbital parameters via an 'impulse' parameter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 32 publications
3
67
0
1
Order By: Relevance
“…Real form factors are complicated by the presence of several components but can be simplified by assuming they are all equal. Covington et al (2008) have shown that Eq. (22) with Cremn = C1 = C2 = 0.5C12 is in good agreement with the sizes of the remnants of dissipationless mergers in hydrodynamic simulations, though the best fit for Cremn/C12 depends on the simulations' assumptions for the initial orbits.…”
Section: Mergersmentioning
confidence: 99%
See 2 more Smart Citations
“…Real form factors are complicated by the presence of several components but can be simplified by assuming they are all equal. Covington et al (2008) have shown that Eq. (22) with Cremn = C1 = C2 = 0.5C12 is in good agreement with the sizes of the remnants of dissipationless mergers in hydrodynamic simulations, though the best fit for Cremn/C12 depends on the simulations' assumptions for the initial orbits.…”
Section: Mergersmentioning
confidence: 99%
“…19 show the maximum increase in σe that dissipation could plausibly cause in bulges with Mstars < ∼ 10 11 M⊙. They correspond to a contraction in radius by a factor of two (the maximum value allowed by Covington et al 2008). Fig.…”
Section: The Faber-jackson Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…We show this in 3 bins of stellar mass (relative to M Ã % 10 11 M , or M Ã V ¼ À21). Solid (dashed) lines show the mean (AE1 ) correlation, following the analytic solution for dissipational mergers and fits to our simulation in Covington et al (2008). We show the Spearman rank correlation coefficient and probability of the null hypothesis P null (no correlation) in each panel.…”
Section: Assessing the Role Of Dissipation In Observed Systemsmentioning
confidence: 99%
“…We can also construct this plot with the starburst mass fraction f sb of the best-fitting simulation as the independent variable (instead of the fitted extra light mass fractions f extra ) and find a correlation of the same nature. Given two progenitors of known size and mass, it is straightforward to predict the size of the remnant of a dissipationless merger, simply assuming energy conservation (see, e.g., Barnes 1988); in the case of a dissipative merger, Covington et al (2008) use the impulse approximation to estimate the energy loss in the gaseous component, followed by collapse in a self-gravitating starburst. This yields a detailed approximation as a function of, e.g., initial structural and orbital parameters, but if we assume typical initial disk structural scalings and parabolic orbits, it reduces to the remarkably simple approximation…”
Section: Assessing the Role Of Dissipation In Observed Systemsmentioning
confidence: 99%